Levels of Physical Fitness and Weight Status in Children and Adolescents: A Comparison between China and Japan - Li, Yuqiang (Int J Environ Res Public Health, 2020)
This study compared the physical fitness level and weight status of children and adolescents in China and Japan. Children and adolescents aged 7–18 years were recruited (China: n = 5660; Japan: n = 5660). Physical fitness was assessed using seven core items—grip strength, 30-s sit-ups, standing long jump, sit-and-reach, 20-s repeated straddling, 20-m shuttle run test, and 50-m dash. A physical fitness index (PFI) was calculated by adding all items’ Z-scores. We conducted comparisons of PFI and its distribution, each physical fitness item, and weight status for individuals from China and Japan across all ages. The PFI was lower in China than in Japan for all age groups, with an especially large difference at age 18 years for boys (a difference of 9.05) and girls (a difference of 9.10) (p < 0.001). The same result was seen for the seven items. The PFI distribution for children and adolescents was more disperse among those in Japan than among those in China. Obesity prevalence was 2.84 times higher in China than in Japan. An inverted U-shaped relationship was observed between physical fitness and nutritional status. Children and adolescents showed markedly lower physical fitness and higher obesity prevalence in China than in Japan.